Implementation of Youth Integrated Healthcare Center in the Prevention of Stunting Incidents in the Kekeran Village of Badung Regency, Indonesia - I Nyoman Wirata; I Gusti Agung Ayu Novya Dewi; Ni Made Dwi Purnamayanti; Nı Komang Erny Astiti; Nı Wayan Suarniti (Atatürk University, 2024)
Objective: Youth posyandu is a youth empowerment activity that can reduce the prevalence of stunting through pre-marital care. At the time during the Covid 19 pandemic, youth posyandu was not carried out. The purpose of the research is to identify the input, process and output of the implementation of youth posyandu activities, and identify knowledge and nutritional status of the adolescent women. Methods: This research is a mixed method research. Six qualitative research informants, and 32 quantitative data respondents. Data were collected through in-depth interviews and questionnaires. Research data analysis is descriptive analysis and distribution of frequency data knowledge and nutritional status of adolescent daughters. Results: The results show that the input from the implementation of the program is sufficient, seen from the presence of the programme implementation guidelines and the use of the funds that have been verified, the support of means, resources. The output indicates that the activities are going as planned, but the coverage of the participants is still 80%. The knowledge of youth posyanduis partially good and the nutritional status of the teenage daughter is mostly normal. Conclusion: The program input is sufficient, the process is running well, has managed. Should be corrected during the Covid 19 pandemic and the output of the program implementation is largely in line with the plan. Knowledge is partly good and nutritional status is mostly normal.